2007
DOI: 10.1007/s10654-007-9129-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cleft palate alone and cleft palate with accompanying defects

Abstract: The epidemiology of cleft palate with multiple defects is often thought to be different from that of cleft palate alone, but there are few empirical data on this question. We explored this in a population-based data set created by combining data from two sources: the 1.8 million live births recorded from 1967 to 1998 in the Norwegian Birth Registry, and the two Norwegian surgical centers that repair cleft palate. Accompanying defects were identified from either source. Stratified analysis and logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 27 publications
(27 reference statements)
2
28
0
7
Order By: Relevance
“…8,9,14,15,19,20,[22][23][24][25]29,31,36,37,42,43,47,53,59,60,70,72,[75][76][77][78][79] Whilst three studies described potential bias or efforts to identify bias in Section 2, 41,76,80 12 studies reported having used statistical methods to control for confounders. 10,24,[30][31][32]42,[46][47][48]78,79,81 In Section 4, 23 studies properly reported the studies limitations 4,9,10,21,24,32,34,35,38,41,42,44,…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,14,15,19,20,[22][23][24][25]29,31,36,37,42,43,47,53,59,60,70,72,[75][76][77][78][79] Whilst three studies described potential bias or efforts to identify bias in Section 2, 41,76,80 12 studies reported having used statistical methods to control for confounders. 10,24,[30][31][32]42,[46][47][48]78,79,81 In Section 4, 23 studies properly reported the studies limitations 4,9,10,21,24,32,34,35,38,41,42,44,…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The most categories of maternal age used were 19 or <20, 20-24, 25-29, 30-34, 35-39, >39 or 40 years. 4,16,25,29,30,36,37,42,52,58,68,69,73,78,79,81,85 Ten studies described methods to evaluate subgroups and interactions, mainly between groups of maternal and paternal ages. 10,19,21,36,[46][47][48]52,79,81 The outcome data were not reported in three case-control studies 43,66,86 and eight cross-sectional studies.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…35 El labio y paladar hendido en su variedad no sindrómi-ca representa el 70% de estas alteraciones, se presenta como un defecto aislado mientras que el sindrómico representa el 30% y está asociado a otras anormalidades estructurales. 2,13,11 La prevalencia de las hendiduras orales ha sido relacionada con el número de gestaciones de la madre, siendo más prevalente en los casos donde la madre es multípara. Además, se ha observado una relación con la edad materna, y con los antecedentes familiares ya que es más frecuente en los sujetos que tienen historia familiar de haber sufrido el evento.…”
Section: Epidemiologíaunclassified
“…El primero hace referencia al LPH que se acompaña o es parte de otros síndromes en un mismo niño y se presenta en un 30% de los casos; el segundo, se presenta de manera aislada, es decir, como una alteración única y ocurre en el 70% de los casos. 2,13 Independientemente, si es LPHns o LPHs, el niño es susceptible a una serie de complicaciones que afectan su desarrollo. Lee y colaboradores observaron que los niños con LPHns presentaban, principalmente, deficiencia en el peso y que después de ser sometidos a los procedimientos quirúrgicos, éste se normalizaba.…”
unclassified
“…In one study (Bille et al 2005), both a high maternal age and a high paternal age were found to be associated with the occurrence of cleft lip with or without cleft palate, while a higher paternal age, but not a higher maternal age, was shown to increase the risk of having a child with cleft palate only. A Norwegian study confirmed the effect of the father's age, but not of the mother's age, on the incidence of cleft palate (Harville et al 2007). In another study (Materna-Kiryluk et al 2009), advanced maternal and paternal ages were both shown to be independently associated with congenital heart defects; furthermore, a higher paternal age was found to be positively associated with the incidence of cleft palate and cleft lip.…”
Section: Introductionmentioning
confidence: 90%